2010
DOI: 10.1016/j.cell.2010.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Activation-Induced Cytidine Deaminase Targets DNA at Sites of RNA Polymerase II Stalling by Interaction with Spt5

Abstract: Summary Activation induced cytidine deaminase (AID) initiates antibody gene diversification by creating U:G mismatches. However, AID is not specific for antibody genes. Off-target lesions can activate oncogenes or cause chromosome translocations. Despite its importance in these transactions little is known about how AID finds its targets. To address this, we performed an shRNA screen. We found that Spt5, a factor associated with stalled RNA polymerase II (Pol II) and single stranded DNA (ssDNA), is required fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
416
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 327 publications
(441 citation statements)
references
References 90 publications
24
416
1
Order By: Relevance
“…However, pausing of RNAPII during transcription can lead to more extensive exposure of ssDNA in the transcription bubble (Gómez‐González & Aguilera, 2007) and a number of studies have suggested that transcriptional pausing is also a key mechanism to attract AID to the IgV mutation domain (Kenter, 2012). Supporting this idea, AID has been physically linked to RNAPII through its ability to binding the RNAPII‐associated processivity factor Spt5 (Pavri et al , 2010), the PAF complex (Willmann et al , 2012) and components of the exosome (Basu et al , 2011), the latter observation providing a potentially elegant solution to the problem of AID targeting both strands of DNA, as the exosome could facilitate exposure of the template strand in addition to the coding strand.…”
Section: Discussionmentioning
confidence: 99%
“…However, pausing of RNAPII during transcription can lead to more extensive exposure of ssDNA in the transcription bubble (Gómez‐González & Aguilera, 2007) and a number of studies have suggested that transcriptional pausing is also a key mechanism to attract AID to the IgV mutation domain (Kenter, 2012). Supporting this idea, AID has been physically linked to RNAPII through its ability to binding the RNAPII‐associated processivity factor Spt5 (Pavri et al , 2010), the PAF complex (Willmann et al , 2012) and components of the exosome (Basu et al , 2011), the latter observation providing a potentially elegant solution to the problem of AID targeting both strands of DNA, as the exosome could facilitate exposure of the template strand in addition to the coding strand.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that Spt5, the component of another elongation factor DSIF, promotes SHM (9). To test whether SSRP1 knockdown affects Spt5 loading, we tested the Spt5 occupancy with SSRP1-depleted cells.…”
Section: Resultsmentioning
confidence: 99%
“…Spt5 binding is almost proportional to the level of RNAPII at genetic loci (9,17). Similarly, H3K4me3 serves as a general marker of active chromatin (18), and the Paf1 complex acts as a scaffold for the H3K4 trimethylase complex and is required for the elongation-promoting activity of the DSIF complex (19).…”
Section: Aid | Ssrp1mentioning
confidence: 99%
See 2 more Smart Citations